Profile of Creative Thinking Skills on Junior High School Students in Science Learning by Gender - Ida Madyani; Sri Yamtinah; Suryadi Budi Utomo (Scientiae Educatia: Jurnal Pendidikan Sains, 2019)
Creative thinking is one of the essential skills in science learning. Creative thinking skills become a source of strength in the development, invention, and investigation to face the obstacles in the 21st century. This study aimed to determine the creative thinking skills of junior high school students in science learning by gender. This study used descriptive analysis with quantitative data. Data collection by tests, interviews, and observation sheets. The participants of this study were 94 students from three different schools consisting of 35 male and 59 female students. The sampling technique uses purposive sampling. Indicators of critical thinking are fluency, flexibility, originality, and elaboration. Creative thinking skills in this study divided into three categories: high, medium, and low. The result of this study showed that the male students have a high percentage of flexibility, the average percentage in both originality and fluency, and a low percentage in elaboration. Female students have a high percentage in fluency, the medium percentage in elaboration, and a low percentage in both originality and flexibility.